Determining male sexual offender subtypes using cluster analysis - Rosenberg, Ruth (Journal of quantitative criminology, 1988)
Although sexual offenders comprise a heterogeneous group, there are few subtyping schemes that are simultaneously meaningful to clinicians and empirically validated. This investigation used cluster analysis to derive subtypes of rapists and child molesters using five dimensions: substance use, life management skills, antisocial behavior, sexual aggression, and offense-related impulsivity. Twelve subtypes were derived and compared with subtypes described in the literature and with one rationally constructed typological system. Of the nine subtypes that were considered clinically distinct and meaningful, two manifested high aggression, four low aggression, and three moderate aggression. The study determined distinctive, recognizable subtypes of sexual offenders and established some degree of external and descriptive validity for them. Content issues regarding the subtypes as well as several of the issues and problems involved in classification research are discussed.